2018
DOI: 10.1186/s12873-018-0158-5
|View full text |Cite
|
Sign up to set email alerts
|

Ambulance use is not associated with patient acuity after road traffic collisions: a cross-sectional study from Addis Ababa, Ethiopia

Abstract: BackgroundAfrica accounts for one sixth of global road traffic deaths—most in the pre-hospital setting. Ambulance transport is expensive relative to other modes of pre-hospital transport, but has advantages in time-sensitive, high-acuity scenarios. Many countries, including Ethiopia, are expanding ambulance fleets, but clinical characteristics of patients using ambulances remain ill-defined.MethodsThis is a cross-sectional study of 662 road traffic collisions (RTC) patients arriving to a single trauma referral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…May occur in or out of the hospital setting, and may involve physicians, pre-hospital providers and other licensed professionals. Bystanders may also provide emergency care (for cardiopulmonary resuscitation for example), if well trained Emergency Medical Services (EMS) Emergency Medical Services (EMS), a coordinated system of EC response [25], have been identified by the WHO as an effective public health intervention for addressing the disproportionately high burden of maternal mortality [26][27][28][29][30][31][32][33][34][35]. Across the African region, prehospital emergency care systems are being developed to provide care and transportation for critical, timesensitive obstetric and other emergencies for diverse populations of varying socioeconomic strata [26,[28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Appropriatenessmentioning
confidence: 99%
“…May occur in or out of the hospital setting, and may involve physicians, pre-hospital providers and other licensed professionals. Bystanders may also provide emergency care (for cardiopulmonary resuscitation for example), if well trained Emergency Medical Services (EMS) Emergency Medical Services (EMS), a coordinated system of EC response [25], have been identified by the WHO as an effective public health intervention for addressing the disproportionately high burden of maternal mortality [26][27][28][29][30][31][32][33][34][35]. Across the African region, prehospital emergency care systems are being developed to provide care and transportation for critical, timesensitive obstetric and other emergencies for diverse populations of varying socioeconomic strata [26,[28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Appropriatenessmentioning
confidence: 99%
“…Contextualized, informal lay provider networks as employed on a small scale by some parts of Madagascar, Uganda, Ghana, and southern Nigeria [ 71 75 ] can be strengthened to decrease prehospital trauma mortality rates; however, this should not be used to excuse the absence of tier-2 systems which ideally represent the highest quality of prehospital surgical care [ 76 ]. The percentage of injured patients that arrive at health facilities by ambulance in SSA varies widely by country and facility, from 59% in Ethiopia [ 77 ] to 5.9% in Zambia [ 78 ] and 5% in Mozambique [ 79 ].…”
Section: Search Resultsmentioning
confidence: 99%
“…Nearly all participants (53/58 (91%)) indicated that they would like further training in the use of ETCO 2 , with 18 of the 58 respondents indicating that they considered themselves out of date or that their initial training was not sufficient with respect to capnography. When asked how training should be delivered the following key words were identified in the analysis: continuous medical education [14] , online training [9] , lectures [12] , workshops [7] , and practical training [6] .…”
Section: Resultsmentioning
confidence: 99%
“…Despite the widespread international acceptance, and use of capnography, there is little published research on its use in Africa outside of SA, even in national referral hospital anaesthetic practice, capnography is apparently rarely available or used in East and West Africa [9] , [10] , [11] . Prehospital services are in their infancy in much of Africa, and looking to other develop their systems currently [12] , [13] , [14] . Rational use of this important, although still expensive resource, and including it in training programs is important yet understudied.…”
Section: Introductionmentioning
confidence: 99%